Voluntary intake by sheep and goats of Gliricidia sepium fed in three states and at three levels of supplementation to a basal diet of Panicum maximum - Smith, Jimmy W.; Larbi, Asamoah; Jabbar, M.A.; Akinlade, J. (Springer, 1995)
Crude protein content and in sacco dry matter (DM) loss after 72 h of incubation in West African Dwarf (WAD) sheep and goats of fresh, wilted and dried leaves of Gliricidia sepium were compared. Additionally, voluntary DM intakes by WAD sheep and goats of G. sepium leaves presented in the fresh, wilted and dried states at 10,20 and 30 percent levels of supplementation were investigated in two'separate experiments. The crude protein content and DM loss from dried leaves were relatively lower than fresh and wilted leaves. At all levels of supplementation, the voluntary DM intakes of fresh and wilted leaves by WAD sheep and goats were relatively higher than dried leaves. The results suggest that G. sepium leaves should be fed either in the fresh or wilted states to WAD sheep and goats, at levels between 20 and 30 percent of the total daily DM allowance.